Comparison of Mechanical Properties of Samples Fabricated by Stereolithography and Fused Deposition Modelling - Bayraklılar, Mehmet Said; Buldu, Abdulkadir; Koçak, Muhammed Tayyip; Ülkir, Osman; Kuncan, Melih (My University, 2023)
Additive manufacturing (AM) technology has attracted significant attention with the rapid fabrication of 3D parts for various applications. The two most popular techniques in this technology, Fused Deposition Modelling (FDM) and Stereolithography (SLA), make it possible to produce functional parts with complex shapes quickly and cheaply. Determining the mechanical properties of the parts fabricated by these methods is important in terms of efficient operation in the relevant fields. In this study, forty-five test specimens were fabricated using three different polymer materials (UVR, PLA, and ABS) in SLA and FDM type 3D printers, including tensile, compression, and 3-point bending tests. Samples are printed at a 75% fill rate according to ASTM standards. Experimental studies were carried out to determine the mechanical properties of the samples. Among the samples, the highest strength values in tensile, compression and bending test samples made of UVR material were 60.39 MPa, 127.74 MPa and 118.35 MPa, respectively. In addition to mechanical properties, hardness, and SEM analyses were performed to examine the surface roughness, surface topography, and composition of the samples.
Keywords: Additive manufacturing; Tensile test; Stereolithography; Fused deposition modelling; Compression test; 3-point bending test